Cost-Effectiveness Analysis of the Drugs Used in Oncology Department at a Tertiary Care Hospital in India - Arvind Kumar; Ranjeet Kumar; Vikas Saxena (Advances in Public Health)
Conclusion: The present research shows the correlation between cost and other dependent variables utilizing various statistical analytic approaches. The cost-effectiveness of cancer treatment must be evaluated individually, taking into account the patient’s health, choices, and overall prognosis.